Balancing Oncological Care and Quality of Life: Diagnostic and Therapeutic Strategies for Chemotherapy-Induced Cardiotoxicity—A Narrative Review - Alexandra Huiduc; Ovidiu Popa-Velea; Adriana Mihaela Ilieșiu (Journal of Clinical Medicine, 2026)
Background: Cardiovascular complications of cancer therapy may affect patients far beyond conventional measures of cardiac function, yet their relationship with health-related quality of life (HRQoL) remains incompletely defined. This review examined how cardiovascular status and cardiotoxicity-related interventions relate to HRQoL across cancer treatment and survivorship. Methods: Twenty-one studies were reviewed and reassessed according to four research questions: established cardiovascular disease or cardiac dysfunction and HRQoL; subclinical cardiovascular abnormalities and subsequent HRQoL; interventions targeting cardiotoxicity with HRQoL assessment; and supportive interventions improving HRQoL without demonstrated cardioprotection. Evidence was additionally considered across diagnostic, pharmacological/cardioprotective, exercise, and supportive-care domains. Results: The available evidence revealed a clinically relevant pattern. Established cardiovascular disease or cardiac dysfunction showed the clearest association with poorer HRQoL, particularly in physical domains, whereas evidence linking subclinical abnormalities to subsequent patient-reported deterioration was sparse. Most studies evaluated interventions, including cardioprotective pharmacological strategies and exercise-based approaches, but improvements in HRQoL were not consistently accompanied by, or attributable to, demonstrated cardioprotection. Exercise and supportive interventions were also associated with improvements in functional or patient-reported outcomes in some studies, independently of demonstrable cardiovascular benefit. Across domains, substantial heterogeneity in populations, cardiovascular measures, interventions, HRQoL instruments, and study designs limited direct comparison and causal interpretation. Conclusions: Cardiovascular health and HRQoL appear closely interconnected, but the available evidence does not establish a consistent link between cardiovascular injury and subsequent changes in HRQoL. The literature is richer in prevention and intervention studies than in longitudinal assessment of the patient-reported consequences of cardiovascular injury. Larger prospective studies incorporating standardized serial cardiovascular assessment and HRQoL as a predefined primary endpoint are needed to establish temporal relationships and clinically meaningful cardiovascular determinants of HRQoL.